Hybrid winding function method for inductance analysis of a line start synchronous reluctance machine - Redjem Rebbah; Mohamed Yazid Kaikaa; Loubna Boudjelida (Institute of Advanced Engineering and Science, 2022)
In recent years, there has been renewed interest in line-start synchronous reluctance machines (LSSRMs) due to their simple construction, magnet-free rotor, and low cost. To improve control performance, design optimization, and fault diagnostic analysis of these machines, it requires accurate estimation of their electromagnetic characteristics using detailed and time-consuming finite element analyses (FEAs). In this paper, inductances and electromagnetic torque of the LSSRM were calculated using the combination of winding function analysis and conformal mapping instead of FEA. The hybrid approach can be applied to the prediction of motor behavior, taking into account all space harmonics of the air-gap permeance without any restriction on the rotor saliencies and topologies. The influence of the core saturation, stator slots, and rotor bars were also considered. The results obtained by simulations were compared with FEA in terms of accuracy and computational time.